USING A COGNITIVE BEHAVIORAL FRAMEWORK TO TRAIN STAFF SERVING INDIVIDUALS WHO EXPERIENCE CHRONIC HOMELESSNESS. Issue 5 (July 2016) - Pontoski Taylor, Kristin; Cunningham, Amy; Schultz, Luke; Jager‐Hyman, Shari; Sposato, Rosanna; Evans, Arthur; Beck, Aaron T.; Creed, Torrey A.
Abstract : Training in evidence‐based practices may better prepare providers to address the effect of behavioral health concerns on chronic homelessness. Through the Beck Initiative, a community–academic partnership, case managers ( n = 19) were selected to incorporate a cognitive‐behavioral therapy (CBT) framework into services for chronic homelessness at seven sites in Philadelphia, PA. Details of the training components and development are presented. This training program demonstrated feasibility within these low‐demand shelter settings (79% completed training, 10% left employment during training, 10% did not complete). Feedback measures indicated positive feedback regarding acceptability, usefulness, and quality of training. Planned discharges from the shelters were significantly more frequent in the 6 months posttraining compared with the 6 months before training. The CBT framework shows early promise for improving services for people experiencing chronic homelessness. This program also demonstrates the benefit of involving community stakeholders and academic partners to address one aspect of chronic homelessness.